A Talon Cusp on Fused Teeth Associated with Hypodontia: Report of a Unique Case - Dinesh Rao, B; Hegde, Sapna (European Journal of Dentistry, 2010)
Fusion and talon cusps are rare developmental dental anomalies affecting both primary and permanent dentitions. Talon cusps normally occur on the palatal surface of permanent maxillary incisors, while fused teeth are more common in the primary anterior dentition. An understanding of these dental anomalies and their associated problems are important to provide prophylactic measures, thereby preventing or minimizing possible complications. This paper presents a unique case of fused mandibular permanent incisors with a lingual talon cusp associated with hypodontia of an adjacent tooth. (Eur J Dent 2010;4:75-80)
Keywords: Talon cusp; Dental fusion; Hypodontia; Dental anomalies